PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT NSC FINANCE CABANG BANTUL - Jefry Satria Rukmandanu (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to study transformational leadership style on employee performance; the effect of work motivation on employee performance; the influence of work discipline on employee performance; and understand the most dominant variable between transformational leadership style, work motivation and work discipline on employee performance. Primary data were collected using questionnaire assistance from 53 employees of PT NSC Finance, Bantul Branch. Data were analyzed using multiple linear regression. The hypothesis is proposed by the t test, the F test and the questionable variable are dominantly supported by a comparison of standardized regression coefficients. The results of the analysis show all the independent variables namely transformational leadership style, work motivation and positive and significant work discipline on employee performance both partially and simultaneously at α = 5%. The most dominant variable influencing employee performance is work motivation variable.